Gauguin's skirt - Eisenman, Stephen F. (Thames and Hudson, 1997)
Gauguin's Skirt is about contemporary Tahitians and a long-dead French painter, sex today and sex in the late nineteenth century, and colonialism new and old. It is concerned with Paul Gauguin's practices as an artist and with the practice of daily life in fin de siecle Polynesia. Written on the boundary between art history and anthropology, Gauguin's Skirt enters the domains of biography and mystery.